Recurrent infections in partial complement factor I deficiency: evaluation of three generations of a Brazilian family - Grumach, Anete; Leitão, M F; Arruk, V G; Kirschfink, Michael; Condino-Neto, A (Clinical & experimental immunology, 2006)
We report here on the evaluation of a factor I-deficient Brazilian family (three generations, 39 members) with strong consanguinity. The complete factor I-deficient patients (n = 3) presented recurrent respiratory infections, skin infections and meningitis; one of them died after sepsis. They presented an impaired total haemolytic activity (CH50), low C3, low factor H and undetectable C3dg/C3d. Partial factor I deficiency was detected in 16 family members (normal low cut-off value was 25 µg/ml). Respiratory infections were the most common clinical occurrence among partial factor I-deficient relatives. Two of them were submitted to nephrectomy following recurrent urinary tract infections. An additional two heterozygous relatives presented with arthritis and rheumatic fever. Apparently, patients with partial factor I deficiency are also at higher risk for recurrent infections. Vaccination against capsulated bacteria and the eventual use of prophylactic antibiotics should be considered individually in this patient group.
Gesehen am 15.02.2021